THE ROLE OF DIPLOMACY IN FOREIGN POLICY FORMULATION - Alier, Dr. Gabriel; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Diplomacy is often confused with foreign policy ,but the terms are not synonymous. Diplomacy is the chief, but not the only, instrument of foreign policy, which is set by political leaders, though diplomats (in addition to military and intelligence officers) may advise them. Foreign policy establishes goals, prescribes strategies, and sets the broad tactics to be used in their accomplishment. It may employ secret agents, subversion, war, or other forms of violence as well as diplomacy to achieve its objectives. Diplomacy is the principal substitute for the use of force or underhanded means in statecraft; it is how comprehensive national power is applied to the peaceful adjustment of differences between states. It may be coercive (i.e., backed by the threat to apply punitive measures or to use force) but is overtly nonviolent. Its primary tools are international dialogue and negotiation, primarily conducted by accredited envoys (a term derived from the French envoyé, meaning “one who is sent”) and other political leaders. Unlike foreign policy , which generally is enunciated publicly, most diplomacy is conducted in confidence, though both the fact that it is in progress and its results are almost always made public in contemporary international relations[1].The purpose of foreign policy is to further a state’s interests, which are derived from geography, history, economics, and the distribution of international power. Safeguarding national independence, security, and integrity of territorial, political, economic, and moral viewed as a country’s primary obligation, followed by preserving a wide freedom of action for the state. The political leaders, traditionally of sovereign states, who devise foreign policy  pursue what they perceive to be the national interest, adjusting national policies to changes in external conditions and technology. Primary responsibility for supervising the execution of  policy  may lie with the head of state or government, a cabinet or a nominally non-governmental collective leadership, the staff of the country’s leader, or a minister who presides over the foreign ministry, directs  policy  execution, supervises the ministry’s officials, and instructs the country’s diplomats abroad[2].